Opioid-free anesthesia for postoperative recovery after video-assisted thoracic surgery: A prospective, randomized controlled trial - Wang, Xu-ru; Jia, Xiao-yu; Jiang, Yan-yu; Li, Zhen-ping; Zhou, Qing-he (Frontiers in Surgery, 2023)
Background: Opioid-based anesthesia is a traditional form of anesthesia that has a significant analgesic effect; however, it causes nausea, vomiting, delirium, and other side effects. Opioid-free anesthesia with dexmedetomidine and lidocaine has attracted widespread attention. The goal of this study was to compare opioid-free anesthesia (OFA) and opioid-based anesthesia (OBA) on the effect of postoperative recovery of patients after video-assisted thoracic surgery. Methods: Eighty patients who underwent video-assisted thoracic surgery were assigned to receive either opioid-free anesthesia (OFA group) or opioid-based anesthesia (OBA group) according to random grouping. The primary outcome of the study was the quality of recovery-40 scores (QoR-40) 24 h postoperatively. The secondary outcome measures were numerical rating scale (NRS) scores at different time points 48 h postoperatively. In addition to these measurements, other related parameters were recorded. Results: Patients who received opioid-free anesthesia had higher QoR-40 scores (169.1±5.1 vs. 166.8±4.4, p=0.034), and the differences were mainly reflected in the patients’ comfort and emotional states; however, the difference between the two groups was less than the minimal clinically important difference of 6.3. We also found that NRS scores were lower in the OFA group than in the OBA group at 0.5 h (both p<0.05) and 1 h (both p<0.05) postoperatively and the cumulative 0–24 h postoperative dosage of sufentanil in the OBA group was higher than that in the OFA group (p=0.030). There were no statistically significant differences in postoperative nausea and vomiting (PONV) (p=0.159). No surgical or block complications were observed between groups. Conclusion: Opioid-free analgesia potentially increased postoperative recovery in patients who underwent video-assisted thoracic surgery.